Zakót as a financial instrument for poverty reduction and human development from the perspective of maqsôd as-sharô’ah in line with the Qar’ónic tafasôr - ,, Mohammad Habibullah; Sharofiddin, Ashurov (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), 2019)
The purpose of this study is to provide a general exposition on the concept and management of zakÉt, in particular applying it to poverty reduction as an important panacea in today’s widespread situation of financial calamity of Muslim countries. The aim of this study is to analyze the implication of zakÉt as a financial instrument for poverty reduction and human development from the prospective of Maqasid Sharia’h in line with the Quranic Tafaser. The methods of data collection for this research involved library research through reading and content analysis of Quranic verses and other secondary sources. Therefore, the researcher attempts to investigate the failure of zakÉt management and distribution or any other factors that may have caused its inability to realize its objective towards poverty reduction in Muslim countries. Thus, this study will focus how the collection and distribution of zakÉt complement the Islamic doctrine of socioeconomic neutrality, which is incorporated in the responsibilities of the authorities who are entrusted to lessen poverty and uplift the poor from the poverty line. This refers to ability to fulfil basic needs such as food, shelter, education and health. As a result, poverty will be assumed to have been eradicated when the basic needs are fulfilled and minimum level of living for everyone has been satisfied.